A gamified approach to promoting empathy in children. Issue 3 (10th June 2020) - Saleme, Pamela; Dietrich, Timo; Pang, Bo; Parkinson, Joy
Abstract : Purpose: Gamification has gained popularity in social marketing research; however, its application remains limited to a few contexts, and relatively little is known about how innovative gamification technologies such as augmented reality can be applied to social marketing programme design. This paper aims to demonstrate the application of gamification to a social marketing pilot programme designed to increase children's empathy and empathic behaviour. Design/methodology/approach: Informed by social cognitive theory (SCT), a mixed-method research design was adopted using pre- and post-programme surveys ( n = 364) to assess effectiveness using paired samples t -test. Qualitative data included observations, participant's questions and a feedback activity at the end of the programme. A thematic analysis was undertaken to examine the data and detect meaningful insights. Findings: Children's affective empathy and empathic behaviour outcomes were improved following the pilot programme. However, no effects were observed for cognitive empathy and social norms. Thematic analysis revealed three themes to further improve the game: developmentally appropriate design, user experience and game design. Research limitations/implications: Findings demonstrated challenges with the application of SCT outlining a disconnect between the design of the gamified programme and theory application. Practical implications: This study provides initial evidence for the application of innovative gamification technologies to increase empathy in children. Originality/value: To the best of the authors' knowledge, this paper is the first to examine how a gamified social marketing programme can increase empathy in children.